Polymer nanocomposite-based strain sensors with tailored processability and improved device integration - Costa, Pedro (2018)
Due to its easy processability and elastomeric properties, the triblock copolymer styrene-butadiene-styrene (SBS) is an excellent matrix for the development of piezoresistive polymer composites, mostly for larger strain composites. Piezoresistive sensors based in SBS and conductive fillers have been processed by scalable methods, extrusion and spray printing, allowing the measurement of large deformations up to 20% of strain with low mechanical hysteresis in loading-unloading cycles. The carbon nanotube (CNT) reinforcement increases the mechanical properties (maximum stress and strain) and provides electrical properties to the composites. Extruded and spray printed carbon nanotubes (CNT)/SBS composites show a piezoresistive sensibility (gauge factor) up to 4 and 2, respectively. Their percolation threshold is near 6 and 1 wt.%, for extruded and spray printed methods, respectively. The excellent piezoresistive reproducibility, processability and easy integration in structures and devices show the suitability of those materials for applications, as demonstrated by the implementation of a hand glove able to measure the movement of the fingers. The electronic readout systems develop allows, in real-time, measure and save the data points of each piezoresistive sensor in a remote platform. Thus, the present paper demonstrates the optimisation, processing by scalable methods, and integration of piezoresistive polymer based materials for force and deformation sensor applications.